The Use of Social Media in Improving EFL Learner Writing Skills - Dewi, Kartika Puspa; Rizal, Daviq (Universitas Muhammadiyah Jember, 2023)
Early on social media was only used as a method of communication; however, as diverse learning requirements and media emerged, EFL students began to use social media as a learning medium, specifically for learning English. This trend is expected to continue to an indefinite time limit. In addition to developing their English language abilities, EFL leaner can improve their listening, speaking, reading, and writing skills. This research seeks to determine how social media can assist EFL students in improving their writing skills. This study identified 118 articles using a qualitative systematic review; however, only 11 articles matched the research topic and were included in the analysis. Those articles find out from the world’s databases. Looking to the outcomes of this research, students of English as a foreign language (EFL) can improve their writing abilities and keep their motivation levels high while studying by making use of the features that are made available on social media platforms. Students of English as a foreign language (EFL) can evaluate their writing skills by contributing to every posting page on each platform. More investigations can be conducted to investigate the benefits of writing on Instagram, such as creative writing in the classroom and research on a global scale.